Continuous glucose monitoring system versus self-monitoring blood glucose in type 1 diabetes mellitus children (RoSEC): a randomized controlled trial - Muhd Helmi, Muhd Alwi; Hussain, Suhaimi; Bachok, Norsaadah (2019)
Background A single centre, randomized, parallel-group controlled trial was conducted involving twenty-two type one Diabetes Mellitus (T1DM) patients with the mean age of 13.8 years assigned to either intervention or control group.